A NEW LECANICEPHALIDEAN CESTODE ENDOPARASITE ON TRYGON SEPHEN FROM RATNAGIRI, INDIA - DANDWATE, R.R.; JADHAV, B.V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The present communication deals with a new species of the genus Polypoceplalus, Braun (1878) i.e. P. mirkurwarensis n. sp., it is differentiated from the earlier known species of the genus with the characters like spherical scolex, tentacles 10-12 in number, presence of neck, testes five in number, ovary elongated, uterus oval and vitellaria follicular.